99mTc-68Ga-ICG-Labelled Macroaggregates and Nanocolloids of Human Serum Albumin: Synthesis Procedures of a Trimodal Imaging Agent Using Commercial Kits. (22nd January 2020) - Persico, Marco Giovanni; Marenco, Manuela; De Matteis, Gianluca; Manfrinato, Giulia; Cavenaghi, Giorgio; Sgarella, Adele; Aprile, Carlo; Lodola, Lorenzo
Abstract : Recent developments in sentinel lymph node (SLN) and radio occult lesion localization (ROLL) highlight the need for a multimodal contrast agent, providing better presurgical PET imaging and improved intraoperative mapping thanks to fluorescence detection. For this reason, we have studied a trimodal SLN/ROLL targeting agent ( 99m Tc- 68 Ga-ICG) with commercially available kits of macroaggregated or nanocolloidal albumin (MA/NC-HSA). 68 Ga PET imaging does provide better spatial resolution and makes it possible to predict signal intensity during surgery. The presence of 99m Tc assesses the efficacy of these compounds in vitro and also during the surgery procedure. The aim of this study was to optimise the labelling and tagging of these two radiopharmaceuticals and assess their yields and stability. Kits of MA/NC-HSA particles (Pulmocis® and NanoAlbumon®) were used for sequential radiolabelling with 99m Tc and 68 Ga. Fluorescent tagging was performed using indocyanine green, a tricarbocyanine dye. The ITLC radiochemical purity of the trilabelled MA/NC-HSA was >95%. Fluorescent purity was measured by scanning the strips with a PhotoDynamicEye probe. Finally, in vitro stability tests, performed with DTPA and human serum solutions, assessed the efficacy of fluorescent tagging and radiolabelling.